2009
DOI: 10.1007/s00439-009-0737-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of association of rs2200733 on chromosome 4q25 with atrial fibrillation and ischemic stroke in a Chinese Han population

Abstract: Atrial fibrillation (AF) is the most common arrhythmia in the clinical setting and an independent risk factor for stroke. Approximately 10 million Chinese people are affected by AF, but the genetic basis is largely unknown. A recent genome-wide association study in Iceland identified association between SNP rs2200733 on 4q25 and AF; however, many independent replication studies are essential to unequivocally validate this association. To assess the association between rs2200733 and AF as well as that between r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
3
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 28 publications
1
74
3
8
Order By: Relevance
“…3 A small replication study in the Chinese Han population failed to show association for ischemic stroke. 7 The 4q25 variants had been shown previously to confer risk for atrial fibrillation (AF). 8 The 4q25 haplotype block consists of Ϸ1.5 million bp without any known genes.…”
mentioning
confidence: 99%
“…3 A small replication study in the Chinese Han population failed to show association for ischemic stroke. 7 The 4q25 variants had been shown previously to confer risk for atrial fibrillation (AF). 8 The 4q25 haplotype block consists of Ϸ1.5 million bp without any known genes.…”
mentioning
confidence: 99%
“…rs2200733 was the most significantly associated polymorphism. The association between rs2200733 and AF has since been replicated in GWAS involving cohorts of Asian patients as well as patients of European ancestry [25,26,60,61]. Neither variant at the 4q25 locus has been correlated with AF risk factors such as obesity, hypertension, or myocardial infarction.…”
Section: Genome Wide Association Studies In Afmentioning
confidence: 93%
“…In sum, these studies consistently showed the association between rs2200733 and AF but not with rs10033464. Shi et al (Shi et al 2009) also carried out a case-control study with AF patients and non-AF controls to conWrm the association of rs2200733 on chromosome 4q25 with AF in a Chinese Han population. They conWrmed a signiWcant association with OR = 1.81 between rs2200733 and AF (Shi et al 2009).…”
Section: Common Variants On 4q25mentioning
confidence: 98%